Plan de negocios para la creación de una empresa de alquiler de maquinarias y equipos de construcción, en la ciudad de Quevedo, año 2014 - Soliz Piedrahita, Karla Cristina (2015)
The project is based on the career prospects designed in the Race of Marketing, characterized by a study and design of a company where aspects of planning, management, control and business development, in line with the Vision and Mission incorporated Race, capable of providing solutions to specific problems, such as job creation, creativity for the development of constructions, suitable to develop skills in a quality and service processes. In this context it is proposed to answer the following research question: What is the impact of a business plan for the creation of an equipment rental company building in the city of Quevedo, 2014? The overall objective set for this research is: Making a business plan for starting a business of rental equipment and construction machinery in the city of Quevedo, 2014. The feasibility of the project is determined by the financial study which was established with an initial investment of assets 826,919.39 where funding is divided into own contribution 248,075.82 which corresponds to 30% and financial support through credit corresponding Bank of 578,843.57 70% of the initial investment. The financial evaluation through the formulas used to establish the feasibility of achieving excellent results project was a positive net present value (NPV) of 620,514.53 obtaining an internal rate of return (IRR) 48.71% having a balance of 257,835.90 and cost - benefit $ 1.75